Earnings of Hispanic Men: The Role of English Language Proficiency - McManus, Walter; Gould, William; Welch, Finis (Journal of Labor Economics, 1983)
The size and rapid growth of the Hispanic population in the United States raise many questions about the effects of language on the process of economic assimilation. This paper uses data on earnings for 1975 to explore the role of English language proficiency in the assimilation of Hispanic men into the U.S. labor market. The results are strong: differences associated with English language skills explain virtually all of the Hispanic wage differences usually attributed to ethnicity, national origin, and time in the United States. The analysis is completed by relating the measure of English language proficiency to assimilation-related variables.